Caprini score combined with thrombotic molecular markers for predicting DVT in patients with traumatic fractures - Zhengsheng Wu; Yaoqiang Du; Xiaofeng Cai; Qian Xu (Scientific Reports)
Abstract Deep vein thrombosis (DVT) is one of the important factors leading to death in patients undergoing fracture surgery. This study aims to investigating the predictive value of the Caprini score combined with thrombus molecular markers for the risk of DVT in patients after traumatic fracture surgery. A total of 342 patients who underwent surgery for traumatic fractures were included in the study. The patients were divided into two groups based on the occurrence of DVT after surgery: the DVT group (n = 57) and the non-DVT group (n = 285). A univariate analysis and logistic regression analysis were conducted on clinical factors and laboratory indicators that might be associated with DVT in patients with traumatic fractures. A predictive model for DVT risk was then constructed by combining thrombus molecular markers with the Caprini score. The median age of all patients was 65 years (54–75 years), the postoperative Caprini score was 9 (6–11), and the length of hospital stay was 11 days (8–16 days). In univariate analysis, age (P = 0.029), postoperative Caprini score (P < 0.001), and length of hospital stay (P = 0.009) were significantly associated with the occurrence of DVT. Logistic regression analysis showed that the risk of developing DVT increased with higher postoperative Caprini scores (P < 0.001), longer hospital stays (P = 0.024), and higher PIC levels (P = 0.046). Among these, the postoperative Caprini score was the most effective factor for diagnosing DVT, with an area under the curve (AUC) of 0.814 (P < 0.001) and a diagnostic cutoff of 11 points. The overall diagnostic efficacy of individual thrombus molecular markers from highest to lowest was TM, DD, PIC, t-PAIC, and TAT, with all except TAT showing statistical significance. The combined diagnostic efficacy of the postoperative Caprini score and PIC also showed statistical significance (AUC = 0.869, P < 0.001). Thrombus molecular markers combined with the postoperative Caprini score have potential predictive value for the risk of DVT in patients after traumatic fracture surgery.